Conforto e qualidade ambiental no habitat do idoso - Barbosa, Ana Lúcia de Góes Monteiro (2002)
Taking the increase of urban population in Brazil into consideration, the research proposes a special focus on elderly users, into the theme Environmental Comfort. From the interdisciplinary revision of the thematic concept in Environmental Comfort and Gerontology, it ransons their interfaces in order to permit estabilish the necessities and habitat project 's guidelines to elderly persons. It is introduced a comfort and quality study in elderly habitat in tropical climate, face their specific characteristics of mobility and ability. A survey accomplished in a habitat institution for the elderly in Niterói city complement the work, evaluating into higrotermic, visual and acustic points of view. At last, it related some guidelines and recomendations to residential design for spaces frequently used by the elderly persons. It is noticed that in this research, the elderly is not distinguished by his age, but from a whole of specific characteristics of mobilities, abilities and independence.